Controls of Multimodal Wave Conditions in a Complex Coastal Setting. Issue 24 (23rd December 2017) - Hegermiller, C. A.; Rueda, A.; Erikson, L. H.; Barnard, P. L.; Antolinez, J. A. A.; Mendez, F. J.
Abstract: Coastal hazards emerge from the combined effect of wave conditions and sea level anomalies associated with storms or low‐frequency atmosphere‐ocean oscillations. Rigorous characterization of wave climate is limited by the availability of spectral wave observations, the computational cost of dynamical simulations, and the ability to link wave‐generating atmospheric patterns with coastal conditions. We present a hybrid statistical‐dynamical approach to simulating nearshore wave climate in complex coastal settings, demonstrated in the Southern California Bight, where waves arriving from distant, disparate locations are refracted over complex bathymetry and shadowed by offshore islands. Contributions of wave families and large‐scale atmospheric drivers to nearshore wave energy flux are analyzed. Results highlight the variability of influences controlling wave conditions along neighboring coastlines. The universal method demonstrated here can be applied to complex coastal settings worldwide, facilitating analysis of the effects of climate change on nearshore wave climate. Key Points: A hybrid statistical‐dynamical method is introduced to assess nearshore wave climate in complex coastal settings Relative contributions of swells propagating from distant, discrete generation regions and local seas vary largely over small coastal scales Neighboring coasts are sensitive to different large‐scale atmospheric patterns